Image of the pre-Islamic poem - Ali AlHabooby (آداب الرافدين, 1975)
Pre-Islamic poetry was organized in many weights represented by the seas that Khalil bin Ahmed Al-Farahidi devised, all of them are fifteen seas - even though some of these seas prevailed over poetry at that time, such as the long, simple, abundant, complete, long, and shaky. The pre-Islamic poem dealt with different topics, moved between them, and committed to expressing them, with fixed methods, specific images and artistic traditions. She did not deviate from it and did not seek to change it. This is because these purposes, themes, traditions, and expressive templates were the fruit of long previous efforts, which we cannot track because history has preserved for us only the last episode of it, represented by what we have left of the poetry of the century preceding the emergence of Islam. These effects, while they remained, reveal to us the nobility and maturity, and depict their admiration for what they have reached, and their belief that what they have attained represents the end beyond which nothing is sought.